Responses of communities to social tensions - Srivastava, Vinay Kumar (2002)
The author perceives most of the social tensions as inter-community and interest group clashes. The article projects the anthropological angle to this phenomenon which cuts across time and space. It focuses on an interesting aspect of communities' system of bracing against the tension-prone situations and their evaluation of loss and gain even in containing and encountering these. The most important response, according to the author, comes from the communities in form of the role they play in negotiating their mutual ties. - Reproduced.
Keywords: Social conflicts